Stealing MySpace : the battle to control the most popular website in America - Angwin, Julia (New York : Random House, 2009)
Pulitzer Prize-winning journalist Julia Angwin chronicles the rise of MySpace and sheds light on the dizzying backroom deals that allowed Rupert Murdoch to snatch this Internet powerhouse from Viacom's grasp.
Stealing MySpace -- Circle of friends -- Rising from the ashes -- The trailer park of the internet -- Struggling to survive -- The Fakester revolution -- Building MySpace -- The boardroom coup -- The fix-it-later philosophy -- Operation show time -- Are we missing the next Google? -- Tsunami -- Independence -- The king of spyware -- Schmuck insurance -- The game is on -- Project ivory -- Holding a tiger by the tail -- A fine line between risqué and dirty -- "A place for friends" -- Pebble Beach -- War against Web 2.0 -- Number one in every market -- Beyond the banner ad -- The FaceBook revolution -- MySpace 2.0 -- Digital identity.
Includes bibliographical references (p. [271]-356) and index.
Keywords: MySpace (Firm); News Corporation; Internet industry -- United States; Online social networks -- History